Percentage Of Giblets And Digestive Organs of Jowo Super Chicken Fed Lemon Grass (Cymbopogon Nardus) Flour In The Rations - Alam Anugerah Ilahi; Dede Kardaya; Agung Puji Haryanto (Jurnal Peternakan Nusantara, 2026)
Lemon grass contains phytochemical compounds contained in it, namely saponins, flavonoids, polyphenols, and alkaloids. The purpose of this study was to examine the effect of citronella meal on the percentage of giblets and digestive organs of super jowo chickens (joper). This research was conducted in Padasuka village, Ciomas, Bogor regency, West Java from July to September 2023. This study used a completely randomized design (CRD) consisting of 5 treatments and 4 replicates, for each replicate or cage unit consisting of 5 joper chickens. The treatments in this study were R0 = basic ration (control), R1 = basic ration + 2% citronella meal, R2 = basic ration + 4% citronella meal, R3 = basic ration + 6% citronella meal, R4 = basic ration + 8% citronella meal. Data were analyzed using analysis of variance (ANOVA), and continued with Duncan's test if the research data showed significantly different results (P<0.05). The variables observed in this study were the percentage of heart, liver, gizzard, small intestine, and ceca. The results of this study showed that the addition of lemon grass meal (Cymbopogon nardus) in the ration until 8% was not significantly effect (P>0.05) to the percentage of giblets and digestive organs of joper chickens. The results of this study suggest that the addition of lemon grass meal in the ration of joper chickens is given more than 8%.